Glyceroltriheptanoate (GTH) occurrence in animal by-products: a monitoring study to minimise safety-related risk of misuse. Issue 6 (3rd June 2022) - Pederiva, Sabina; Avolio, Rosa; Morello, Sara; Abete, Maria Cesarina; Marchis, Daniela
Abstract: Early in this century, the crisis connected to the spread of bovine spongiform encephalopathy caused a great concern related to the use of animal by-products (ABPs). According to the Commission Regulation (EU) No 1069/2009, these materials are classified in three categories according to their related risk. In 2011 Commission Regulation (EU) No 142/2011 established that meat and bone meal (MBM) and fat deriving from ABPs not intended for human consumption (category 1 and 2) are required to be permanently marked with glyceroltriheptanoate (GTH), at a minimum concentration of 250 mg kg –1 of fat, while category 3 processed animal proteins (PAPs) must not contain this compound. PAPs are bio resources, which could be used in a renewable and regenerative way in a circular economy model for a conscious usage of raw materials. The aim of this study was to provide information on GTH occurrence in MBM and, if any, in PAPs. Samples were collected from 2017 to 2021 and analysed by GC-MS. Detected non-compliant samples were exclusively of MBM category 1 and 2, probably due to the addition of an inadequate amount of GTH during the manufacturing processes. These results highlighted the importance of National Monitoring Programs as a useful tool to minimise safety related risk due to the misuse of GTH. Thus, investigating the critical points in feed supply-chain and sharing the information on its occurrence may help to improve animal and human wellness and safety.